1998
DOI: 10.1097/00003226-199801000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Human Donor Corneas Preserved for Longer Than 4 Weeks

Abstract: From these data, we conclude that long-term organ culture in a closed system is limited to approximately 6 weeks and thereby confirm the clinical results of Früh and Böhnke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
3
16
1
1
Order By: Relevance
“…Analysis of metabolic changes in organ-cultured donor corneas showed that the corneas recover during organ culture, especially during the first 2 weeks. Improved biochemical values were found during the first 4 weeks and acceptable conditions for only up to 6 weeks [8,9]. After 4 weeks of culture, the entire population of keratocytes was found to be still alive, but in contrast to the situation after 2 weeks only very few mitotic keratocytes could be detected [7].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Analysis of metabolic changes in organ-cultured donor corneas showed that the corneas recover during organ culture, especially during the first 2 weeks. Improved biochemical values were found during the first 4 weeks and acceptable conditions for only up to 6 weeks [8,9]. After 4 weeks of culture, the entire population of keratocytes was found to be still alive, but in contrast to the situation after 2 weeks only very few mitotic keratocytes could be detected [7].…”
Section: Introductionmentioning
confidence: 85%
“…The main criterion for the quality of a donor cornea is the endothelial cell density. During culture, a progressive decrease in endothelial cell density occurs that may result in total endothelial necrosis if the storage period exceeds 6 weeks [8]. However, clinical results comparable with those obtained using corneas in culture for shorter periods have been reported after keratoplasty using donor corneas cultured for up to 7 weeks and with endothelial cell density still greater than 2000 cells/mm 2 [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The lentiviral vector pseudotyped with VSV-glycoprotein has a broad target cell range allowing the vector to transduce a diversity of cells, such as human hematopoietic stem cells, 11,12 rat hippocampal cells, 13,14 human macrophages, 15 rat liver and muscle cells, 16 and rat retinal cells. 17 Unlike other transplanted tissues, the cornea can be maintained in vitro for days, 18,19 allowing ex vivo transduction before transplantation. 3 The permanent genetic modification of corneal cells may benefit patients with a wide variety of corneal defects.…”
mentioning
confidence: 99%
“…In our study, no routine media exchange was performed until deswelling or day 28 of organ culture, when some corneas were further preserved for emergency grafting purposes [22]. Media samples were taken in a sterile bank using a sterile needle through the rubber infusion stoppers (sterilized prior to use), which were protected by pre-sterilized knurled caps during storage (similar to infusion bottle caps), and additionally surface-decontaminated prior to sampling.…”
Section: Discussionmentioning
confidence: 99%